#IchbinHannah and the fight for permanent jobs for postdocs: How a fictitious postdoc (almost) triggered a fundamental reform of German academia. (31st January 2022) - Dirnagl, Ulrich
Abstract : Regarding postdocs as disposable labour with limited contracts is damaging for science. Universities need to offer them better career perspectives.